2018
DOI: 10.1007/s10549-018-05103-w
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stem cell crosstalk with chemo-residual breast cancer cells: implications for tumor recurrence

Abstract: PurposeMost triple-negative breast cancer (TNBC) patients exhibit an incomplete response to neoadjuvant chemotherapy, resulting in chemo-residual tumor cells that drive tumor recurrence and patient mortality. Accordingly, strategies for eliminating chemo-residual tumor cells are urgently needed. Although stromal cells contribute to tumor cell invasion, to date, their ability to influence chemo-residual tumor cell behavior has not been examined. Our study is the first to investigate cross-talk between adipose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A study by Park et al, 2013, shows that endotrophin secreted by adipose tissue confers resistance to cisplatin in BC mouse models [ 266 ]. Lyes et al, 2019, showed that ADSC secretes FGF2 which activates ERK signaling, thereby promoting the proliferation of chemotherapy residual TNBC cells through the SDF-1α/CXCR4 signaling pathway [ 267 ]. Furthermore, Yeh et al, 2017, showed that ADSC promotes doxorubicin resistance in TNBC by CXCL1 secretion, which upregulates the expression of ABCG2, an ATP binding cassette (ABC) transporter [ 268 ] responsible for multidrug resistance in cancers [ 269 ].…”
Section: Therapeutic Approaches For Bc and The Importance Of Adipomentioning
confidence: 99%
“…A study by Park et al, 2013, shows that endotrophin secreted by adipose tissue confers resistance to cisplatin in BC mouse models [ 266 ]. Lyes et al, 2019, showed that ADSC secretes FGF2 which activates ERK signaling, thereby promoting the proliferation of chemotherapy residual TNBC cells through the SDF-1α/CXCR4 signaling pathway [ 267 ]. Furthermore, Yeh et al, 2017, showed that ADSC promotes doxorubicin resistance in TNBC by CXCL1 secretion, which upregulates the expression of ABCG2, an ATP binding cassette (ABC) transporter [ 268 ] responsible for multidrug resistance in cancers [ 269 ].…”
Section: Therapeutic Approaches For Bc and The Importance Of Adipomentioning
confidence: 99%
“…ADSCs can also upregulate the epithelial-mesenchymal transition markers of breast cancer cells, such as fibronectin, alpha smooth muscle actin, and vimentin, and promote the ability of tumor metastasis and invasion [ 89 , 92 , 93 ]. Through paracrine manner by secreting FGF-2 and activating extracellular signal-regulated kinase (ERK), ADSCs could drive tumor cell proliferation at the chemo-residual triple-negative breast cancer [ 94 ]. ADSCs might even fuse with tumor cells to form hybrid cells which possessed stronger proliferation and metastasis capabilities [ 95 ].…”
Section: Basic Functions Of Adscsmentioning
confidence: 99%
“…In addition, breast cancer cells treated with the conditioned medium from human adipose tissue-derived macrophages exhibited enhanced malignant phenotypes, and these macrophages over-expressed a cluster of cancer-associated genes, with the C-X-C chemokine ligand 1 (CXCL1) and C-X-C chemokine ligand 5 (CXCL5) being mostly upregulated 18 . Moreover, dysregulation of adipose tissue-derived stem cells (ADSCs) has been associated with breast cancer progression and metastasis, possibly via the expression of multiple C-X-C chemokines 19 21 . As these adipose tissue-derived cells may have crucial roles in promoting breast malignancy by interacting with cancer cells in the breast tumor microenvironment, identifying and targeting their pathogenic molecular pathways have emerged as a potential strategy for breast cancer treatment 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%